Pemanfaatan Saluran Pemasaran Terintegrasi Bagi Pelaku Usaha Di Negeri Lilibooi Maluku Tengah - Rainier Hendrik Sitaniapessy; Victor Ernest Huwae; Feky Reken; Siska Jeanete Saununu (LPPM STIKOM Tunas Bangsa, 2023)
Indonesia's economic growth, especially in the field of micro, small, and medium enterprises (MSMEs), has decreased from year to year. One of them has an impact on business actors in Lilibooi State, Central Maluku, who are experiencing sluggish sales and suspended animation. Even though the natural resources in Lilibooi Country are very abundant, including nutmeg and cloves, this is due to the absence of an integrated marketing channel model. This service aims to find out the use of integrated marketing channels for every business actor in Lilibooi Country. This activity was carried out for one day and is expected to provide an understanding of the benefits and an integrated marketing channel system that can be implemented by business actors in order to increase sustainable economic growth in Negeri Lilibooi, Central Maluku.